2014
DOI: 10.3390/d6010018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Microbial Community Structure in Freshwater Stream Sediment in a North Carolina River Basin

Abstract: This study examined seasonal differences in microbial community structure in the sediment of three streams in North Carolina's Neuse River Basin. Microbes that reside in sediment are at the base of the food chain and have a profound influence on the health of freshwater stream environments. Terminal-Restriction Fragment Length Polymorphism (T-RFLP), molecular fingerprint analysis of 16S rRNA genes was used to examine the diversity of bacterial species in stream sediment. Sediment was sampled in both wet and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 52 publications
3
21
1
3
Order By: Relevance
“…In fact seasonal variation of microbial communities has been observed in various environments including soils (Rasche et al 2011;Shi et al 2013), marine sediments (Du et al 2011), reservoirs (Henne et al 2013) and stream sediments (Bucci et al 2014). It was reported that multiple potential factors including water chemistry (Shabarova and Pernthaler 2010), plant diversity, soil moisture, organic matter content, and soil temperature could impact microbial community composition (Rasche et al 2011;Shi et al 2013).…”
Section: Temperature-induced Seasonal Variation Of Bacterial Communitiesmentioning
confidence: 97%
“…In fact seasonal variation of microbial communities has been observed in various environments including soils (Rasche et al 2011;Shi et al 2013), marine sediments (Du et al 2011), reservoirs (Henne et al 2013) and stream sediments (Bucci et al 2014). It was reported that multiple potential factors including water chemistry (Shabarova and Pernthaler 2010), plant diversity, soil moisture, organic matter content, and soil temperature could impact microbial community composition (Rasche et al 2011;Shi et al 2013).…”
Section: Temperature-induced Seasonal Variation Of Bacterial Communitiesmentioning
confidence: 97%
“…Different bacterial groups are specific in their activity and their habitat. They are very sensitive toward the changes occurring in the environment, and therefore, any kind of environmental stress results in a variation in the microbial community structure in the environment [51]. Our results are capable to explain the behavior of microbial community under different environmental stress conditions.…”
Section: Microbial Community and Covaried Environmental Factorsmentioning
confidence: 68%
“…This seasonal fluctuation in the number of bacterial taxonomic groups was earlier documented in the Delaware drainage basin (Hullar et al 2006), Liu et al (2012), in the Changjiang Estuary and East China Sea and in the Arabian Sea (Bandekar et al 2016). Mary et al (2006) and Bucci et al (2014) suggested that a variety of different environmental parameters (temperature, nutrient concentration, liability of organic matter, primary production and grazing bacteria) favoured different groups of polygenetic bacteria at different times of the year. Gammaproteobacteria, Flavobacterium-Cytophaga and Marine alpha-cluster were dominant in the water of the studied water basin in summer.…”
Section: Discussionmentioning
confidence: 99%
“…Among organisms inhabiting the sediment-water interface the most numerous and those with high productivity and enzymatic activity are microorganisms, mainly aerobic and anaerobic bacteria with different metabolic potential (Xia et al 2014;Wei et al 2016). These prokaryotic organisms play a key role in ecological functions and processes such as regulation, assimilation, accumulation, export, decomposition, degradation, enzymatic hydrolysis, re-mineralization and transformation of the largest part of organic matter accumulated in SWI (Bucci et al 2014;Wei et al 2016). According to Tanase et al (2009) and Liu et al (2012), in order to fully understand the role of bacteria in the functioning of the sediment-water interface, it is necessary not only to determine their secondary production, enzymatic activity, respiration processes, morphological differentiation and physiological properties but also to determine their abundance and taxonomic diversity.…”
Section: Introductionmentioning
confidence: 99%